Pengaruh Rehabilitasi DAM Lodan terhadap Produksi dan Pendapatan Petani (Studi Kasus di Desa Lodan, Kab. Rembang) - Supanggyo Supanggyo (Caraka Tani: Journal of Sustainable Agriculture, 2004)
The research objectives were to identify Dam Lodan rehabilitation and influencing to production and farm income. The research with survey method, and descriptive analysis. The research was carried out Lodan village, Sarang District, Rembang. The research findings indicated that production and farm income to increased, after the Dam Lodan rehabilited. Padi to increased 171,75% and farm income 169,75%. The sensitivity analysis indicated, when the construction cost increasing 10% and the benefit decreasing 10%, EIRR= 12,03, NPV= 872,740 and B/C Ratio= 1,45.